1999
DOI: 10.1177/01461672992512001
|View full text |Cite
|
Sign up to set email alerts
|

Accountability for Consequential Decisions: Justifying Ethical Judgments to Audiences

Abstract: College students believed that they were judges in a real cheating case (in actuality, it was fictitious) under adjudication by a student honor court. Participants recommended harsher punishment after being led to believe that they would explain their decisions in a face-to-face meeting with (a) an official from the honor court, as compared to a meeting with the student or no anticipated meeting (Experiment 1), or (b) the professor who brought the charge of cheating, as compared to a meeting with the student (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 36 publications
1
34
0
1
Order By: Relevance
“…It should be noted that communicators' conformity to the viewpoint of the audience is not necessarily a matter of superficial change. A clear illustration of this has been reported by Pennington and Schlenker (1999) who found that participants adopted the position of the audience even when the anticipated meeting with the audience was unexpectedly cancelled. Kashima (2000;Lyons & Kashima, 2003) recently proposed that such cognitive tuning could also play a key role with respect to stereotype maintenance.…”
Section: Audience Communicationmentioning
confidence: 86%
“…It should be noted that communicators' conformity to the viewpoint of the audience is not necessarily a matter of superficial change. A clear illustration of this has been reported by Pennington and Schlenker (1999) who found that participants adopted the position of the audience even when the anticipated meeting with the audience was unexpectedly cancelled. Kashima (2000;Lyons & Kashima, 2003) recently proposed that such cognitive tuning could also play a key role with respect to stereotype maintenance.…”
Section: Audience Communicationmentioning
confidence: 86%
“…They follow the old adage of 'safety in numbers' or, according to Pennington and Schlenker [37], they conform to the position of the audience.…”
Section: The Principle Of Social Proofmentioning
confidence: 96%
“…Há uma série de pesquisas na área de psicologia social que demonstram a tendência de sintonizarmos as nossas atitudes àquelas das pessoas com as quais interagimos (e.g., PENNINGTON & SCHLENKER, 1999;SINCLAIR et al, 2005). Nós sentimos uma necessidade de pertencer a um determinado grupo e os nossos julgamentos morais são moldados por aquilo que os outros membros do grupo acreditam.…”
Section: Contribuições Da Psicologia Moralunclassified